2016
DOI: 10.1021/acs.jmedchem.6b00084
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine Vaccines: Improvement through Hapten Design

Abstract: Methamphetamine (MA) addiction is a serious public health problem, and current methods to abate addiction and relapse are currently ineffective for mitigating this growing global epidemic. Development of a vaccine targeting MA would provide a complimentary strategy to existing behavioral therapies, but this has proven challenging. Herein, we describe optimization of both hapten design and formulation, identifying a vaccine that elicited a robust anti-MA immune response in mice, decreasing methamphetamine-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 38 publications
0
43
0
Order By: Relevance
“…= 149 g/mol) and contains only one hydrogen-bonding nitrogen atom, it has proven to be one of the more difficult drugs to target by means of a vaccine. Antiserum from vaccinated mice has shown methamphetamine-binding constants (K d ) in the 10 28 to 10 27 M range (Moreno et al, 2011;Miller et al, 2013;Collins et al, 2016). On the other hand, morphinan-based drugs such as heroin and oxycodone are larger (mol.…”
Section: A Drug Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…= 149 g/mol) and contains only one hydrogen-bonding nitrogen atom, it has proven to be one of the more difficult drugs to target by means of a vaccine. Antiserum from vaccinated mice has shown methamphetamine-binding constants (K d ) in the 10 28 to 10 27 M range (Moreno et al, 2011;Miller et al, 2013;Collins et al, 2016). On the other hand, morphinan-based drugs such as heroin and oxycodone are larger (mol.…”
Section: A Drug Selectionmentioning
confidence: 99%
“…The immunostimulatory nature of CpG ODN has prompted the investigation of it as an adjuvant, specifically sequence 2006, also known as 7909, in clinical trials for multiple types of vaccines (Cooper et al, 2004;Valmori et al, 2007;Mullen et al, 2008;Brody et al, 2010;Sogaard et al, 2010). For drugs of abuse vaccines, rodent-specific CpG ODN 1826 has been successfully used as an adjuvant in combination with alum (Pryde et al, 2013;Bremer et al, 2014Bremer et al, , 2016Collins et al, 2016;Kimishima et al, 2017). Compared with alum alone, CpG ODN 1826 + alum could boost hapten-specific titers of Th2-associated (IgG1) and especially Th1-associated (IgG2a) antibody isotypes, resulting in enhanced mitigation of heroin potency (Bremer et al, 2014).…”
Section: B Immunologic Considerationsmentioning
confidence: 99%
“…Incorporation of the peptidic linkers was accomplished using a mild N -hydroxysuccinimide (NHS) ester cross-linking strategy, in order to suppress racemization of the stereogenic carbon in the amphetamine moiety. Coupling of 3 (prepared from 2 as previously described) 31 with NHS-activated esters of Boc-dipeptides followed by Boc cleavage gave intermediates 4a – d (Scheme 1). Subsequent introduction of monomethyl glutarate and saponification to release the acid gave haptens 1 -GG (Gly-Gly), 1 -PG (Pro-Gly), 1 -PA (Pro-Ala), and 1 -A 2 (Ala-Ala).…”
Section: Resultsmentioning
confidence: 99%
“…33 To determine the concentrations and MA-affinities of the resulting Abs, we conducted a competitive radioimmunoassay (RIA) using tritiated MA as the tracer. 31 …”
Section: Resultsmentioning
confidence: 99%
“…Further, we have demonstrated that cytosine-guanine oligodeoxynucleotide (CpG ODN 1826), a TLR9 agonist, and alum function as the most advantageous adjuvant combination, eliciting robust Th1 and Th2 anticocaine immune responses and safely enhancing immunoglobulin G (IgG) antibody titers. 19,[32][33][34][35][36][37] CpG ODNs, which have been extensively studied as vaccine adjuvants in the context of infectious diseases and cancer, enhance antigen (Ag)-specific immune responses by mediating the internalization of Ag into antigen presenting cells (APCs) via receptor mediated endocytosis and stimulating NFκB signaling cascade upon TLR9 binding. [38][39][40][41] Although we have successfully employed anticocaine vaccines, whereby the GNE immunoconjugate, CpG ODN 1826, and alum were mixed immediately prior to vaccination and delivered as individual components, numerous studies have reported significant boosts in vaccine efficacy upon co-internalization of the hapten and CpG ODN by the same APC ( Figure 1).…”
mentioning
confidence: 99%